Nicotinamide mononucleotide reduces melanin production in aged melanocytes by inhibiting cAMP/Wnt signaling - Brito, Sofia; Baek, Jin Myoung; Cha, Byungsun; Heo, Hyojin; Lee, Su Hyun; Lei, Lei; Jung, So Young; Lee, So Min; Lee, Sang Hun; Kwak, Byeong Mun; Chae, Sehyun; Lee, Mi Gi; et al. (Journal of Dermatological Science, 2022)
Background: Nicotinamide mononucleotide (NMN) is a representative anti-aging drug that, after long-term administration in mice, causes an increase in energy and lipid metabolism, improves eye function, immune response, and increases insulin sensitivity. However, the effects of NMN on skin pigmentation are still unknown. Objective: In this study, we aimed to demonstrate the effects of NMN on melanogenesis. Methods: NMN was applied to both young and aged melanocytes, and melanin production, protein expression, and mRNA levels were analyzed. A reconstituted human skin model was used to validate the effect of NMN on melanogenesis in vivo. Results: NMN treatment showed no apparent effects on young melanocytes, however, in aged melanocytes, a marked reduction in melanin production was observed. NMN treatment also efficiently reduced melanin production in a reconstituted human skin with aged melanocytes. Genome-wide analysis showed the downregulation of melanogenesis-related cyclic adenosine monophosphate (cAMP)/Wnt signaling in aged melanocytes. Moreover, NMN treatment downregulated forskolin-induced expression of melanogenesis-related proteins, tyrosinase (TYR), tyrosinase-related protein (TRP)− 1, and TRP-2. Nicotinamide adenine dinucleotide (NAD+), an NMN product within the cells, also reduced cAMP/Wnt signaling in aged melanocytes. SLC12A6 was the most highly expressed gene among the SLC12A family members in melanocytes and was significantly influenced by NMN or NAD+ treatment, indicating that SLC12A6 protein is an NMN transporter in melanocytes. Conclusion: NMN reduces melanogenesis in aged melanocytes by downregulating the signaling of melanogenesis-associated receptors. Therefore, NMN is a human-friendly anti-melanogenic agent with the potential to aid in aging-related hyperpigmentation therapy.
Keywords: Animals; Cyclic AMP; Melanins; Melanocytes; Mice; Monophenol Monooxygenase; NAD; Nicotinamide Mononucleotide; Wnt Signaling Pathway; Aging; CAMP signaling; Melanin; Melanogenesis; Nicotinamide adenine dinucleotide; Nicotinamide mononucleotide; SLC12A; Wnt signaling